Phytoptinae - Chetverikov, Philipp E.; Beaulieu, Frédéric; Cvrković, Tatjana; Vidović, Biljana; Petanović, Radmila U. (Zenodo, 2012)
Subfamily: Phytoptinae Murray Diagnosis . Phytoptids with opisthosoma vermiform and with annuli dorsoventrally subequal in size and number; two pairs of prodorsal shield setae (anterior ve and posterior sc ); tibial solenidion ϕ and opisthosomal setae c1 usually present; spermathecal tubes relatively short. Published as part of Chetverikov, Philipp E., Beaulieu, Frédéric, Cvrković, Tatjana, Vidović, Biljana & Petanović, Radmila U., 2012, Oziella sibirica (Acari: Eriophyoidea: Phytoptidae), a new eriophyoid mite species described using confocal microscopy, COI barcoding and 3 D surface reconstruction, pp. 41-60 in Zootaxa 3560 on page 44, DOI: 10.5281/zenodo.213624